ANALYSIS AND RESEARCH ON THE FRACTURE FAILURE OF A MELT-PUMP GEAR ROTOR - LI YunPeng; LI Feng; WEI Wei; ZHANG HongTao; HAN SiYuan (Jixie qiangdu)
This paper proposed an analysis scheme for the multiple fracture failure of the gear rotor of the melt pump used in the key equipment of a chemical plant.Through the analysis of damage fracture analysis,material property analysis,microstructure analysis and strength checking,the root causes of failure were found,the conclusion of failure was concluded and the improvement scheme was proposed.The analysis results show that the gear rotor of molten pump has some defects in the process of design and machining under complicated conditions,which leads to its frequent failure during operation.By changing its structure,reducing stress concentration,the selection of good materials,improve production processes and other ways to effectively improve the performance of the shaft to meet their functional needs.The results of this research could provide certain reference value in improving the service performance of key transmission parts,especially gear type transmission shafts.